Strong bioaccumulation of a wide variety of PFAS in a contaminated terrestrial and aquatic ecosystem - Ioanna S. Gkika; J. Arie Vonk; Thomas L. ter Laak; Cornelis A.M. van Gestel; Jildou Dijkstra; Thimo Groffen; Lieven Bervoets; Michiel H.S. Kraak (Environment International, 2025)
The widespread use of Per- and Poly Fluorinated Substances (PFAS) in a multitude of industrial and consumer applications, together with their persistence and mobility, has led to global contamination of the abiotic and biotic environment. Nevertheless, important knowledge gaps remain concerning PFAS occurrence and bioaccumulation, with studies tending to focus either on aquatic or on terrestrial ecosystems, with a bias towards the aquatic environment. The aim of the present study was therefore to investigate the distribution and bioaccumulation of various PFAS in a contaminated terrestrial and aquatic ecosystem. Subsequently, it was examined if the calculated bioaccumulation factors are related to PFAS molecular descriptors. Abiotic and biotic samples were collected from the aquatic and terrestrial compartments of a PFAS contaminated ecosystem and screened for 44 compounds. PFAS were present in all environmental compartments with varying profiles and concentrations. Generally, higher concentrations were found in aquatic than in terrestrial biota as well as in animals compared to plants. Biota-to-soil and biota-to-sediment accumulation factors (BSAFs) demonstrated a strong bioaccumulation of PFAS, reaching 96,708 kg sediment/kg biota. Similarly, a high bioconcentration potential from water was observed, with bioconcentration factors (BCFs) reaching 55,597 L water/kg biota. The membrane-water partition coefficient (Kmw) explained PFAS bioaccumulation to some extent, but the still limited understanding of factors driving PFAS bioaccumulation calls for further mechanistic research. Nonetheless, it is concluded that many of the 44 analyzed PFAS strongly bioaccumulate in terrestrial and aquatic primary producers and animals, making these compounds of great environmental concern for the coming decades.